EFEKTIVITAS MEDIA PEMBELAJARAN KARTON, ORIGAMI DAN BENANG PADA MATERI JARING-JARING KUBUS DAN BALOK DI SD - Sitanggang, Andri Kristianto; Alsika, Yesi; Arninda, Mutiya; Ulina, Theresia (Universitas Negeri Medan, 2024)
Students often find learning mathematics difficult in elementary school, especially regarding geometric concepts such as blocks and cube nets. Many students have difficulty understanding these ideas with just verbal explanations and static images. The use of learning media such as cardboard, origami, and thread can help students visualize and understand the web of cubes and blocks better. This media allows students to see and touch three-dimensional models, understand the transformation of two-dimensional shapes, and identify sides and angles more clearly. This research aims to evaluate the effectiveness of this media in increasing students' understanding, interest and learning motivation towards this material, as well as providing insight for educators about the importance of innovation in mathematics learning methods. Data was collected by searching and collecting data from various sources, including books, journals and contemporary research. The method is known as literature study. This research shows that the use of cardboard, origami and thread learning media in teaching cube and block nets in elementary schools provides positive results. The results show that students understand concepts better and are more actively involved in the learning process. Other advantages of using this media are increased creativity and fine motor skills, increased physical and interactive involvement of students, and the ability to visualize abstract concepts.